BIODEGRADATION OF XENOBIOTICS IN FISH: A SYNTHESIS - Júnior, Zenon Ratzlaff (Salão do Conhecimento, 2019)
Work developed at the Regional University of the Northwest of the State of Rio Grande do Sul (Unijuí);